2006
DOI: 10.1097/01.mib.0000217767.98389.20
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in disease phenotypes in patients with Crohnʼs disease

Abstract: We did not detect differences in disease behavior, severity, or joint EIM by race. Although African American patients were more likely to have ileocolonic or colonic disease, these factors did not affect disease behavior or severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 26 publications
3
34
1
Order By: Relevance
“…12,38,41 In the Cross et al 41 study, 73% of the Caucasian participants were diagnosed after the age of 40 (A3). Deveaux et al 12 and Simsek and Schuman 38 also reported that the majority of patients were diagnosed between the ages of 17 and 40 (A2) in both racial groups (Table 3).…”
Section: Crohn's Disease: Age Of Onsetmentioning
confidence: 98%
“…12,38,41 In the Cross et al 41 study, 73% of the Caucasian participants were diagnosed after the age of 40 (A3). Deveaux et al 12 and Simsek and Schuman 38 also reported that the majority of patients were diagnosed between the ages of 17 and 40 (A2) in both racial groups (Table 3).…”
Section: Crohn's Disease: Age Of Onsetmentioning
confidence: 98%
“…7 Since then, numerous other studies examining CD in AA patients using institutional registries also showed no difference in disease severity between AA and non-AA patients. 2,4,8 The question that must then be asked is whether AA patients are receiving lower quality medical management of CD, which predisposes them to non-ideal circumstances at the time of surgical resection. While Nguyen did not show a difference in overall immunosuppressive medication use between AA and white patients, there was a significant decrease among AA patients in the use of infliximab, a targeted biological therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated substantial racial/ethnic differences in the characteristics of IBD in the United States and worldwide [1,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. Little data exists with regard to the prevalence of IBD in Blacks in the United States and in Asians outside Asia [23].…”
Section: Introductionmentioning
confidence: 99%
“…Little data exists with regard to the prevalence of IBD in Blacks in the United States and in Asians outside Asia [23]. There were conflicting findings on whether racial/ethnic groups differ in the distribution and behavior of IBD, with some (but not all) studies showing a more aggressive disease phenotype and worse outcomes without adequate control for risk factors including socioeconomic status [12,13,15,16,17,18,19,21,23]. In addition, significant regional differences were reported in the prevalence of IBD, with it being more frequent in the northern parts of the United States [1,5,25].…”
Section: Introductionmentioning
confidence: 99%